1995
DOI: 10.1021/bi00008a025
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Active Site Cysteine Residue of Rat Liver Mitochondrial Aldehyde Dehydrogenase by Site-Directed Mutagenesis

Abstract: To determine the active site cysteine residue in aldehyde dehydrogenase, we mutated amino acid residues 49, 162, and 302 of recombinantly expressed rat liver mitochondrial (class 2) aldehyde dehydrogenase. The C49A and C162A mutants were fully active tetrameric enzymes, although the C162A mutant was found to be highly unstable. The C302A mutant was also a tetramer and bound coenzyme, but lacked both dehydrogenase and esterase activities. To test for the role of cysteine 302 as a nucleophile, the residue was mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
130
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 150 publications
(134 citation statements)
references
References 53 publications
3
130
1
Order By: Relevance
“…The acylation step involves the formation of a hemithioacetal intermediate via the nucleophilic attack of the catalytic Cys-302 (the amino acid numbering used for the biochemical and structural data is that defined by Wang and Weiner (5)) on the aldehydic function followed by hydride transfer that leads to formation of a thioacylenzyme intermediate and NAD(P)H. This intermediate then undergoes a nucleophilic attack by an activated water or CoA molecule. Over the past 15 years both mechanistic and structural aspects of hydrolytic ALDHs have been studied extensively (5)(6)(7)(8)(9)(10)(11)(12)(13). In addition to local conformational reorganizations of the active site induced by ligand binding that provide the required flexibility for an efficient catalysis (14,15), one of the key aspects of the chemical mechanism of this ALDH family is the substantial conformational flexibility of the NMN moiety of the cofactor and in particular of the nicotinamide ring.…”
Section: Structural Dynamics Associated With Cofactor Binding Have Bementioning
confidence: 99%
“…The acylation step involves the formation of a hemithioacetal intermediate via the nucleophilic attack of the catalytic Cys-302 (the amino acid numbering used for the biochemical and structural data is that defined by Wang and Weiner (5)) on the aldehydic function followed by hydride transfer that leads to formation of a thioacylenzyme intermediate and NAD(P)H. This intermediate then undergoes a nucleophilic attack by an activated water or CoA molecule. Over the past 15 years both mechanistic and structural aspects of hydrolytic ALDHs have been studied extensively (5)(6)(7)(8)(9)(10)(11)(12)(13). In addition to local conformational reorganizations of the active site induced by ligand binding that provide the required flexibility for an efficient catalysis (14,15), one of the key aspects of the chemical mechanism of this ALDH family is the substantial conformational flexibility of the NMN moiety of the cofactor and in particular of the nicotinamide ring.…”
Section: Structural Dynamics Associated With Cofactor Binding Have Bementioning
confidence: 99%
“…sequentially adjacent cysteines are located in the active site; the central member, Cys302, represents the reactive nucleophile (2). (The flanking cysteines are not highly conserved).…”
mentioning
confidence: 99%
“…4B) (26). A glutamate residue might function in both or either of the steps in Aldh (26). Here we showed that the E267A mutant of Hdh possessed only 0.4% of the normal level of Hdh, suggesting that Glu 267 functions as the general base.…”
Section: Discussionmentioning
confidence: 66%
“…Functional Relation between Hdh and Aldh-The deduced amino acid sequence as well as the effect of mutations in Hdh resembled those of Aldh (26,27). We therefore compared the Aldh activities of Hdh and S. cerevisiae Ald4p.…”
Section: Isolation and Identification Ofmentioning
confidence: 99%